Introducing and utilizing innovative technologies in health care systems: a country comparison for peripheral drug-eluting stents in Germany and the USA - Felgner, Susanne; Eckhardt, Helene; Dreger, Marie; Panteli, Dimitra; Henschke, Cornelia (Frontiers in Public Health, 2025)
Drug-eluting stents in the upper leg (DES-UL) are used to treat diseases of the peripheral vessels that are associated with an increased risk of cardiovascular events and are prevalent in industrialized countries such as Germany and the USA. Innovative technologies like DES-UL can bring great benefits to patients, possibly representing the only treatment option. However, they also entail risks since reliable evidence on efficacy/effectiveness and safety are often not available at the beginning of products' life cycles. The aim of the study is to examine utilization of DES-UL in German and US-American hospitals and the development of evidence on efficacy/effectiveness and safety for DES-UL over time. To identify evidence, we conducted a systematic literature search in four biomedical databases (2006–2022) for articles on clinical trials that we categorized by predefined characteristics, including studies' level of evidence (LoE) and population sizes, and the articles' conclusions regarding the technology's efficacy/effectiveness and safety clustered “positive”, “indecisive”, “neutral”, or “negative”. Additionally, we searched for clinical trial registry entries, HTA reports, clinical guidelines, safety notices & recalls, market approval dates, and financing instruments. The utilization of DES-UL was operationalized by annual hospital case numbers. We identified a total of 2,724 publications, of which 123 remained relevant after title/abstract and full text screening. In the early phase of the observation period of DES-UL utilization, the evidence development is characterized by a few articles on studies of low LoE and small population studies. Over time, the body of evidence expands, and articles on studies of high LoE (e.g., RCTs) and larger population sizes were published. Overall, articles with “positive” (n = 41) and “indecisive” (n = 58) conclusions predominate, with especially “positive” conclusions pointing to the efficacy/effectiveness and safety of DES-UL. Overall, utilization of DES-UL in hospitals increased in both Germany and the USA, although not uniformly across all years. An influence of various events on the case numbers' development can be assumed. Health policy makers must ensure that efficacy/effectiveness and safety of technologies are evaluated appropriately. Therefore, robust evidence should be generated and made accessible to clinical and health decision-makers in a timely manner and promptly reflected in clinical guidelines.